Development of chemical element practical workbook based on projects and characters for class xii senior high school - Bajoka Nainggolan; Martin Simamora; Wesly Hutabarat (Jurnal Pendidikan Kimia (JPKim), 2019)
This investigation based on analysis, design, development, implementation, and evaluation (ADDIE) method intended to develop an innovative chemistry laboratory workbook of Chemistry Element integrated with project-based learning and characters. Two chemistry lecturers and teachers respectively selected to validate three local chemistry laboratory workbook and chemistry laboratory workbook developed. Questionnaires distributed to the lecturer and teacher samples and found that content, language, presentation, and feasibility of graphics scores were 3.31, 3.37, 3.22, 3.15 and 3.15 respectively and the average score was 3.26 which means that the chem. Lab workbook developed is very valid. In addition, student samples consisted of 2 classes of grade XII of science students which classified into experimental group  and Controled group. The developed chemistry laboratory workbook and the conventional workbook were tried out to group Experiment and group Controlled respectively. The average scores of student outcomes in group Experiment was higher than group Controled or 87.5%>73.8%. Then the average psychomotor scores of group  Experiment was larger than group controled or 84.64>78.42. In addition, the affective scores of group Experiment was larger than group Controled or 82.78>76.38. The hypothesis tested with one way ANOVA at the significant level of α = 0.05, and found that tCalc > tTable or 4.536 > 1.697 It is concluded that the Innovative chemistry laboratory workbook is highly very good.Keywords: Chemistry laboratory workbook; chemistry element; project-based learning